Crescimento econômico e desigualdade de renda no Brasil: uma análise de painel dinâmico para o período 1985-2002 - Castelar, Pablo Urano de Carvalho (2007)
This dissertation studies the relationship between economic growth and income inequality in the 26 Brazilian states, during the 1985 to 2002 period. The method utilized here was panel data, due to its many advantages, like the possibility of dealing with heterogeneity in micro-units, providing greater variability in micro-units in relation to time, minimizing multicolinearity problems and allowing better analysis of dynamic adjustment. The formulation follows the ones proposed by such works as FORBES (2000), BANERJEE and DUFFLO (2003) and PANIZZA (2002), using data from IPEA for economic growth, income inequality, years of schooling and public investiment. Through regressions that utilized the Arellano-Bond 2-step algorithm, which corrects not only the bias originated from the introduced lagged variable, but also allows a certain degree of endogeneity, it has been observed that inequality affects growth negatively, i.e., the greater the initial income inequality, the lesser the economic growth rate of the corresponding period. Other important results were the positive and robust relationship between schooling and growth and the negative relationship between income and investment with economic growth.